A new method for assessing photovoltaic module cooler based on lifespan effectiveness factor. (July 2022) - Sultan, Sakhr M.; Abdullah, M.Z.
Abstract: Many coolers are available to improve the photovoltaic module (PV) efficiency. Although the lifespan of the PV cooler is an important parameter that should be taken into account to justify manufacturing such products, there is no evidence found in the literature considering this parameter in the PV cooler performance evaluation, making the comparison between the different types of PV coolers becomes difficult. Hence, this short communication is intended to correlate the lifespan of PV with its cooler. It proposes a new technique by introducing a new terminology called the PV cooler lifespan effectiveness factor whose value is depending on the lifespan of both PV and the cooling technique being utilized. This factor is defined as the ratio of the lifespan of the PV cooler to the lifespan of the PV. From results of the current study, it is shown that there is a proportional relationship between the lifespan of the PV cooler and the new factor. On the other hand, there is an inverse proportional correlation between the PV lifespan and the new factor. The values of the new factor are classified. The PV cooler is considered to be a lifespan effective, if the lifespan effectiveness factor is greater than zero and lesser than or equals to unity. Because the lifespan of the material depends on weather conditions which are different from one place to another. Hence, the value of the PV cooler lifespan effectiveness factor will be different. This could be a limitation of the proposed method. It is concluded that the new technique is helpful in categorizing the performance of PV cooler in terms of lifespan effectiveness which may have a potential to be utilized by PV cooler researcher, designer and/or manufacturer.